Factors influencing the adjuvant therapy decision: results of a real-world multicenter data analysis of 904 melanoma patients - Lodde, Georg Christian; Forschner, Andrea Lydia; Hassel, Jessica C.; Wulfken, Lena Margarethe; Meier, Friedegund; Mohr, Peter; Kähler, Katharina C.; Schilling, Bastian; Loquai, Carmen; Berking, Carola; Hüning, Svea; Schatton, Kerstin; et al. (Cancers, 2021)
Adjuvant treatment of melanoma patients with immune-checkpoint inhibition (ICI) and targeted therapy (TT) significantly improved recurrence-free survival. This study investigates the real-world situation of 904 patients from 13 German skin cancer centers with an indication for adjuvant treatment since the approval of adjuvant ICI and TT. From adjusted log-binomial regression models, we estimated relative risks for associations between various influence factors and treatment decisions (adjuvant therapy yes/no, TT vs. ICI in BRAF mutant patients). Of these patients, 76.9% (95% CI 74-80) opted for a systemic adjuvant treatment. The probability of starting an adjuvant treatment was 26% lower in patients >65 years (RR 0.74, 95% CI 68-80). The most common reasons against adjuvant treatment given by patients were age (29.4%, 95% CI 24-38), and fear of adverse events (21.1%, 95% CI 16-28) and impaired quality of life (11.9%, 95% CI 7-16). Of all BRAF-mutated patients who opted for adjuvant treatment, 52.9% (95% CI 47-59) decided for ICI. Treatment decision for TT or ICI was barely associated with age, gender and tumor stage, but with comorbidities and affiliated center. Shortly after their approval, adjuvant treatments have been well accepted by physicians and patients. Age plays a decisive role in the decision for adjuvant treatment, while pre-existing autoimmune disease and regional differences influence the choice between TT or ICI.
Gesehen am 12.07.2021